VD_FINDINFO Jug / 2012 / 148 vom 21. März 2012 - VD Tribunal cantonal (2012)
RETRAIT DU DROIT DE GARDE, DÉTENTIONINCARCÉRATION | 311 al. 1 ch. 1 CC, 311 al. 1 ch. 2 CC, 311 CC, 399a al. 1 CPC, 399a CPC